RESPIRATORY RISK FACTORS IN DEVELOPMENT OF POSTOPERATIVE COMPLICATIONS AFTER THE LUNG RESECTION - Krdzalic, Goran (Bosn J Basic Med Sci, 2004)
The objectives of the study were to identify possible associated respiratory risk factors and to assess incidence of overall postoperative complications after the lung resection. We reviewed 110 patients who underwent lung resections due to malignant neoplasms or benign lung diseases. The risk of postoperative complications was evaluated using the univariate analysis. Results confirmed that low FEV1, postoperative high PaCO2, ASA-status and advanced age were factors associated with development of postoperative complications.